PRODUKSI SERASAH HUTAN LARANGAN ADAT RUMBIO KECAMATAN KAMPAR - Nursal "; Wan Syafi'i; Trisna Wati (Biogenesis, 2016)
ABSTRACT The aim of this research was to determine the Litter Production of The Rumbio Traditional Forest Bans Kampar District in September and November 2014. This research was carried out by measurement of litter production. Litter production research conducted by using stratified random sampling survey, where there are 3 topography that valley, sloping and hilly. Each topography consists of 3 Litter trap with a size of 1x1 meters and is taken from the litter Litter trap container every 2 weeks for 2 months of the study. The parameters observed dropping litter composition of leaves, twigs, flowers and fruits. The results showed that the production of forest litter Prohibition of Indigenous Rumbio 426.6767 gr / m2 / week.Keywords: Litter, Litter Production, Media Interactive Learning